2018
DOI: 10.1099/mgen.0.000149
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of clinical multilocus sequence Type 11 Klebsiella pneumoniae from China

Abstract: The increasing prevalence of KPC-producing Klebsiella pneumoniae strains in clinical settings has been largely attributed to dissemination of organisms of specific multilocus sequence types, such as ST258 and ST11. Compared with the ST258 clone, which is prevalent in North America and Europe, ST11 is common in China but information regarding its genetic features remains scarce. In this study, we performed detailed genetic characterization of ST11 K. pneumoniae strains by analyzing whole-genome sequences of 58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
52
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 50 publications
(78 reference statements)
15
52
1
1
Order By: Relevance
“…It is of interest to highlight that most K types identified in this collection were specifically and uniquely associated with evolutionarily related strains from different countries and recovered from extended periods of time ( Table 1). Some of them correspond to well-established clades from ST11/CG258 (7,21,28), CG15, CG14 (7,20,29), and ST258/CG258 (19,30) identified in previous studies. Occasionally, the same K type was observed in different clones (e.g., K24 in ST11 and ST15, or K64 in ST11 and ST147) ( Table 1).…”
Section: Resultssupporting
confidence: 71%
“…It is of interest to highlight that most K types identified in this collection were specifically and uniquely associated with evolutionarily related strains from different countries and recovered from extended periods of time ( Table 1). Some of them correspond to well-established clades from ST11/CG258 (7,21,28), CG15, CG14 (7,20,29), and ST258/CG258 (19,30) identified in previous studies. Occasionally, the same K type was observed in different clones (e.g., K24 in ST11 and ST15, or K64 in ST11 and ST147) ( Table 1).…”
Section: Resultssupporting
confidence: 71%
“…It is of interest to highlight that most K-types identified in this collection were specifically and uniquely associated with evolutionarily related strains from different countries and recovered from large periods of time ( Table 1 ). Some of them correspond to well-established clades from CG11 7,21,28 , CG15 or CG14 7,20,29 and CG258 19,30 identified in previous studies. Occasionally, the same K-type was observed in different clones (e.g.…”
Section: Resultssupporting
confidence: 70%
“…The link between a particular clone and the K-type had been already recognized for HV Kp , but much less was known regarding the widespread MDR Kp population 5 . Detailed and comprehensive phylogenomics studies have shown a high specificity between certain lineages and particular K-types within CG11, CG14, CG15 or CG258 7,14,15,19,20,28 . In fact, MDR Kp expansion causing hospital or community acquired infections has been driven by clonal selection, since the population is dominated by a small number of lineages exhibiting particular K-types, where phenomes of capsular switching seem to occur sporadically at least in short time-scales (this study, Kaptive database) 6,7,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…According to a report by Dong et al [29], K. pneumoniae utilize an array of virulence factors to colonize and propagate in a host cell. These include at least (a) surface antigen, particularly capsular polysaccharide (CPS, K antigen); (b) siderophores responsible for binding ferric iron secreted by the host's iron-binding proteins; and (c) adherence variables responsible for binding to host cell surfaces, such as fimbriae type 1 and type 3, and non-fimbrial adherence proteins.…”
Section: Discussionmentioning
confidence: 99%